2020
DOI: 10.3390/s20071993
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Development of an Affordable and Practical Light Attenuation Turbidity Sensor for Remote Near Real-Time Aquatic Monitoring

Abstract: Turbidity is a key environmental parameter that is used in the determination of water quality. The turbidity of a water body gives an indication of how much suspended sediment is present, which directly impacts the clarity of the water (i.e., whether it is cloudy or clear). Various commercial nephelometric and optical approaches and products exist for electronically measuring turbidity. However, most of these approaches are unsuitable or not viable for collecting data remotely. This paper investigates ways for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 25 publications
1
27
0
1
Order By: Relevance
“…A parabolic fitting has also been reported in other turbidity sensors like the ones of Reference [28] but having an inverted curvature. Other aspects that must be accounted for when using the sensor are that the reading is influenced by ambient light.…”
Section: Turbidity Sensor Calibrationsupporting
confidence: 63%
See 2 more Smart Citations
“…A parabolic fitting has also been reported in other turbidity sensors like the ones of Reference [28] but having an inverted curvature. Other aspects that must be accounted for when using the sensor are that the reading is influenced by ambient light.…”
Section: Turbidity Sensor Calibrationsupporting
confidence: 63%
“…There are low-cost commercial options if there is no need to measure turbidity with very high accuracy or when its value is less than 1000 NTU. For example, the Robot Gravity turbidity sensor and the TS-300B sensor [28].…”
Section: Tds Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…Gillet 38 found that these analog attenuation sensors could not achieve a sufficiently high resolution to monitor small changes in turbidity. Trevathan 39 recalibrated an appliance sensor (DF Robot SEN0189 Gravity -also attenuation style) and built a waterproof housing for field deployments. However, they did not report on the accuracy of the sensor and were not able to calibrate below 100 Nephelometric Turbidity Units (NTU) (although their test measurements were between 0-20 NTU).…”
Section: State-of-the-art In Low-cost Turbidity Sensingmentioning
confidence: 99%
“…Gillet 37 found that these analog attenuation sensors could not achieve a sufficiently high resolution to monitor small changes in turbidity. Trevathan 38 recalibrated an appliance sensor (DF Robot SEN0189 Gravity - also attenuation style) and built a waterproof housing for field deployments. However, they did not report on the accuracy of the sensor and were not able to calibrate below 100 Nephelometric Turbidity Units (NTU) (although their test measurements were between 0-20 NTU).…”
Section: Introductionmentioning
confidence: 99%